Disinvestment of Public Sector Undertakings in India-An Impact Study - Ramakrishnan, M. K.; R., Sandhya (Indian Journal of Finance, 2010)
In the post independence era, the newly elected Government of our country felt the need for rapid industrialization and rebuilding the nation from its under developed state caused by the British rule. With this end in view, the Government took the lead and introduced five year plans to achieve progress in industry, agriculture, health, education and many other allied sectors contributing to economic development. Governments at central and state level set aside a large portion of its resources for the purpose of promoting Public Sector Undertakings(PSU) which are owned and controlled by the Government. During this period, large number of PSU’s sprang up in entire spectrum of industrial activities ranging from infra development to food and agriculture based sectors. Being a mixed economy, the Government also encouraged private investment in industrial field. The key feature of business activity during that period was the absence of competition between public and private sector through a system of reservation, licensing and import barriers. This has gradually reduced the efficiency of both public and private sector of our country in the later years.